The Effect of Egg shell Flour and Chicken Manure Toward Soil pH, P-availability and Ca of Inceptisol with P-absorption and Ca-absorption on Maize (Zea mays. L) - Desi Simanjuntak; M Madjid Damanik; Bintang Sitorus (Universitas Sumatera Utara, 2016)
The aim of this research was to know the effect of egg shell flour and chicken manure toward soil pH, P- availability and Ca of inceptisol with P-absorption and Ca-absorption on maize (Zea mays L.). The research had been conducted from March to September 2015 at gause, Faculty of Agriculture,University of Sumatera Utara. The method used was Randomized Block Design with 2 factors and 2 replications. The first factor was dosage of chicken manure 0, 18,75, 37,5 and 56,25 g /5 kg (soil) and second factor was dossage of chicken egg shell flour 0, 4, 8, 12 g/5 kg (soil). The result showed that chicken manure was effect significantly to increas soil pH, organic- C, P-availability and P-absorption, Ca-absorption with growth of maize. Application chicken egg shell flour only was significant effect in increasing P-availibility. Interaction manure and chicken egg shell flour was significant effects on plant height and P-availibility.